Heme Oxygenase-1 Delays Gibberellin-Induced Programmed Cell Death of Rice Aleurone Layers Subjected to Drought Stress by Interacting with Nitric Oxide - Wu, Huangming; Zheng, Yan; Liu, Jing; Zhang, Heting; Chen, Huiping (Frontiers in Plant Science, 2016)
Cereal aleurone layers undergo a gibberellin (GA)-regulated process of programmed cell death (PCD) following germination. Heme oxygenase-1 (HO-1) is known as a rate-liming enzyme in the degradation of heme to biliverdin IXα (BV), carbon monoxide (CO), and free iron ions (Fe2+). It is a critical component in plant development and adaptation to environment stresses. Our previous studies confirmed that HO-1 inducer hematin (Ht) promotes the germination of rice seeds in drought (20% polyethylene glycol-6000, PEG) conditions, but the corresponding effects of HO-1 on the alleviation of germination-triggered PCD in GA-treated rice aleurone layers remain unknown. The present study has determined that GA co-treated with PEG results in lower HO-1 transcript levels and HO activity, which in turn results in the development of vacuoles in aleurone cells, followed by PCD. The pharmacology approach illustrated that up- or down-regulated HO-1 gene expression and HO activity delayed or accelerated GA-induced PCD. Furthermore, the application of the HO-1 inducer hematin and nitric oxide (NO) donor sodium nitroprusside (SNP) not only activated HO-1 gene expression, HO activity, and endogenous NO content, but also blocked GA-induced rapid vacuolation and accelerated aleurone layers PCD under drought stress. However, both HO-1 inhibitor zinc protoporphyrin IX (ZnPPIX) and NO scavenger 2-(4-carboxyphenyl0-4, 4, 5, 5-tetramethylimidazoline-l-oxyl-3-oxide potassium salt (cPTIO) reserved the effects of hematin and SNP on rice aleurone layer PCD under drought stress by down-regulating endogenous HO-1 and NO, respectively. The inducible effects of hematin and SNP on HO-1 gene expression, HO activity, and NO content were blocked by cPTIO. Together, these results clearly suggest that HO-1 is involved in the alleviation of GA-induced PCD of drought-triggered rice aleurone layers by associating with NO.